New coronavirus infection (COVID-19) in children: clinical, laboratory and diagnostic aspects - S. Yu. Nosyreva; A. S. Pankov; A. G. Korneev (LLC "Diagnostics and Vaccines", 2021)
The study of a new coronavirus infection (COVID-19) in children is relevant and of interest for practical health care.Purpose: to identify the clinical and laboratory features of COVID-19 in the context of the six-month dynamics of the pandemic in children of the Orenburg region and to formulate recommendations for optimizing the diagnosis of this disease.Materials and methods. A retrospective analysis of 2661 results of detecting SARS-CoV-2 RNA (including 170 children) was carried out on the basis of the microbiological laboratory of the Orenburg State Medical University. Age and sex, structure of preliminary diagnoses, main clinical manifestations, frequency of testing and dynamics of the PCR threshold cycle in September 2020 and January 2021 were assessed.Results. The proportion of children examined in the Orenburg region from September 2020 to January 2021 increased from 4.6 ± 0.6% to 8.1 ± 0.7%. At the same time, the number of PCR + results also significantly increased from 5.0 ± 2.8% to 8.2 ± 2.6% (χ2 = 54.81; p = 0). The average age of children was 9-10 years old. The main reason for referral was pre-hospitalization screening not related to COVID-19. The proportion of PCR + results in this cohort was significantly lower in children than in adults. Among the clinically manifested forms in adults, the leading diagnosis was «pneumonia», and in children «ARVI». In childhood, a predominantly asymptomatic course of the disease was recorded. In children, unlike adults, PCR Ct values did not correlate with the severity and duration of the clinical manifestations of COVID-19.Conclusion. Due to the low diagnostic value of symptoms in children, it is more expedient to focus on epidemiological data and data from the results of laboratory examination methods. When interpreting the results of PCR diagnostics of COVID-19 for prognostic purposes, it is important to take into account the patient's age.